Giant cell tumours of bone treated with denosumab: histological, immunohistochemical and H3F3A mutation analyses. Issue 6 (13th February 2018) - Kato, Ikuma; Furuya, Mitsuko; Matsuo, Kosuke; Kawabata, Yusuke; Tanaka, Reiko; Ohashi, Kenichi
Abstract : Aims: Denosumab, a human monoclonal antibody directed against the receptor activator of nuclear factor‐κB ligand (RANKL), is a therapeutic agent for giant cell tumour of bone (GCTB). Although some studies have reported that denosumab shrinks tumours and induces bone formation, the actual effects of RANKL suppression on GCTB remain unclear. A mutation in the H3 histone family member 3A gene ( H3F3A ) was recently identified as a genetic signature for GCTB. The aim of this study was to investigate the histopathological features and H3F3A mutation status of GCTBs treated with denosumab. Methods and results: Nine biopsy‐diagnosed patients with GCTB, who underwent curettage after neoadjuvant denosumab therapy, were reviewed. Immunohistochemistry for NFATc1 (an osteoclast marker), RUNX2 (an osteoblast marker) and histone H3.3 G34W (G34W, a GCTB marker) was performed; furthermore, H3F3A mutation status was examined with direct sequencing. Before therapy, GCTBs comprised NFATc1+ and RUNX2+ cells. All cases were G34W+ and contained H3F3A mutations. After therapy, the osteoclast‐like giant cells disappeared. Areas of slender spindle cell proliferation and reticular woven bone that were NFATc1− and RUNX2+ replaced the lesions in various proportions. However, all post‐therapy lesions still contained many G34W+ cells and harboured H3F3A mutations. Immunofluorescence double staining revealed that RUNX2+ mononuclear cells coexpressed G34W in pre‐therapy and post‐therapy lesions. Two patients experienced radiologically detected local recurrence within 2 years. Conclusions: Denosumab therapy effectively decreases the number of osteoclastic cells in GCTBs. However, the neoplastic cells with H3F3A mutation survive denosumab treatment and undergo dramatic histological changes in response to this agent.